Prediction model of postnatal renal function in fetuses with lower urinary tract obstruction (LUTO)—Development and internal validation - Duin, Leonie K.; Fontanella, Federica; Groen, Henk; Adama van Scheltema, Phebe N.; Cohen-Overbeek, Titia E.; Pajkrt, Eva; Bekker, Mireille; Willekes, Christine; Bax, Caroline J.; Oepkes, Dick; Bilardo, Caterina M. (John Wiley & Sons Inc., 2019)
Objective: To develop a prediction model of postnatal renal function in fetuses with lower urinary tract obstruction (LUTO) based on fetal ultrasound parameters and amniotic fluid volume. Methods: Retrospective nationwide cohort study of fetuses with postnatally confirmed LUTO and known eGFR. Fetuses treated with fetal interventions such as vesico-amniotic shunting or cystoscopy were excluded. Logistic regression analysis was used to identify prognostic ultrasound variables with respect to renal outcome following multiple imputation of missing data. On the basis of these fetal renal parameters and amniotic fluid volume, a model was developed to predict postnatal renal function in fetuses with LUTO. The main study outcome was an eGFR less than 60 mL/min * 1.73 m2 based on the creatinine nadir during the first year following diagnosis. Model performance was evaluated by receiver operator characteristic (ROC) curve analysis, calibration plots, and bootstrapping. Results: Hundred one fetuses with a confirmed diagnosis of LUTO were included, eGFR less than 60 was observed in 40 (39.6%) of them. Variables predicting an eGFR less than 60 mL/min * 1.73m2 included the following sonographic parameters: hyperechogenicity of the renal cortex and abnormal amniotic fluid volume. The model showed fair discrimination, with an area under the ROC curve of 0.70 (95% confidence interval, 0.59-0.81, 0.66 after bootstrapping) and was overall well-calibrated. Conclusion: This study shows that a prediction model incorporating ultrasound parameters such as cortical appearance and abnormal amniotic fluid volume can fairly discriminate an eGFR above or below 60 mL/min * 1.73m2. This clinical information can be used in identifying fetuses eligible for prenatal interventions and improve counseling of parents.
Keywords: Taverne; Journal Article